DIA Comparative Proteomic Analysis of Retro-oil Fluid and Vitreous Fluid From Retinal Detachment Patients - Shu, Yiyang; Gao, Min; Zhou, Yifan; Liu, Haiyun; Sun, Xiaodong (Frontiers in Molecular Biosciences, 2021)
Objectives: There have been reports of unexplained visual loss following intra-ocular silicone oil(SiO) tamponade in retinal detachment patients, yet the underlying mechanism is unknown. The aim of this study was to investigate mechanisms behind retinal toxicity following intra-ocular SiO tamponade in retinal detachment patients. Methods and Results: Vitreous fluid samples were acquired from 27 patients (27 eyes). Twelve eyes for data-independent acquisition (DIA) were divided into 4 groups: pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RD group), SiO removal after successful retinal reattachment (SO group), cataract surgery after successful retinal reattachment with sterilized air tamponade (FA group), and PPV for epiretinal membrane (ERM group). The remaining 15 eyes were used for enzyme-linked immunosorbent assay analysis. DIA was combined with two-dimensional liquid chromatography-tandem mass spectrometry (LC-MS/MS) to find expression changes in the proteome of vitreous. Mean number mass spectra, statistically differentially proteins, gene ontology (GO), pathways representation and protein interactions were analyzed. GO analysis showed protein categories of synapse organization, cell adhesion, and regulation of cell migration in SO group were differentially expressed compared to control or FA groups (p<0.05). Through Kyoto encyclopedia of genes and genomes (KEGG) analysis, lysosome and cell adhesion were significantly enriched in SO group compared to FA and control groups (p<0.05). Cadherin 2, transferrin and lysosome function may partially contribute to silicone oil related vision loss. Conclusion: Vision loss inducing novel molecular signatures and pathways that may be associated with SiO toxicity were identified. Transferrin may be a potential visual outcome biomarker for SiO tamponade.